Characterization of bovine transcripts preferentially expressed in testis and with a putative role in spermatogenesis - Alves, B. C. A.; Tobo, P. R.; Rodrigues, R.; Ruiz, J. C.; Hossepian de Lima, V. F. M. [UNESP]; Moreira-Filho, C. A. (Elsevier B.V., 2011)
Although the number of genes known to be associated with bovine spermatogenesis has increased in the past few years, regulation of this biological process remains poorly understood. Therefore, discovery of new male fertility genetic markers is of great value for assisted selection in commercially important cattle breeds, e.g., Nelore, that have delayed reproductive maturation and low fertility rates. The objective of the present study was to identify sequences associated with spermatogenesis that could be used as fertility markers. With RT-PCR, the following five transcripts preferentially expressed in adult testis were detected: TET(656) detected only in adult testis; TET(868) and TET(515) expressed preferentially in adult testis but also detected in fetal gonads of both sexes; and TET(456) and TET(262). expressed primarily in the testis, but also present in very low amounts in somatic tissues. Based on their homologies and expression profiles, we inferred that they had putative roles in spermatogenesis. Detection of sequences differentially expressed in testis, ovary, or both, was a useful approach for identifying new genes related to bovine spermatogenesis. The data reported here contributed to discovery of gene pathways involved in bovine spermatogenesis, with potential for prediction of fertility. (C) 2011 Elsevier B.V. All rights reserved.
Keywords: Spermatogenesis; Testis gene expression; Fertility marker; Differential gene expression; qPCR